Small Glaciers of the Putorana Plateau under Climate Change - N. V. Kovalenko; V. V. Popovnin; A. S. Gubanov; A. A. Polyhov; Ye. I. Uspenskaya (Лëд и снег, 2023)
The characteristic feature of the Putorana Plateau is that the glaciological objects here are mostly represented by small glaciers and perennial snow patches. Their regime and morphology have so much common features that separation of these two categories of nival glacial formations from one another is extremely difficult problem. The distinctions between results of earlier studies carried out in the 1970s (the USSR Glacier Inventory estimated local resources at 22 glaciers with a total area of 2.5 km2) and at the beginning of the current century (in 2005, V.A. Sarana identified 61 glaciers with a total area of 7 km2) are too large to make any reliable conclusions about the current trends of the Putoran glaciation. In such conditions, the materials of rare field monitoring work performed on individual nival-glacial bodies become very valuable. Three expedition seasons of 2002–2004 included thorough geodetic and mass-balance measurements on 3 reference objects on the northern ledge of Lama Mts. – Prives (No. 30) Glacier, Marlborough (No. 31) Glacier and Strudoms snow patch. Similar field monitoring was repeated in summer’2019. The change in their configuration according to digital photography data, including the results of the analysis of satellite images, make possible to reveal that interannual fluctuations in the area of each glacier occur due to different vector displacements of its different sections along their entire perimeters. In 2019, the somewhat unexpected good budget state of all 3 monitored objects was detected. It manifested itself in growth of their areas and increased fraction of firn basin as well as in larger water equivalent of the firn residue as this followed from results of snow surveys. This fact contradicts the previous conclusion about the steady trend of deglaciation on the Putorana Plateau. The favourable condition for small glaciers occurred here in 2019 was mainly caused by reduced ablation owing to the weakened insolation that resulted from tremendous forest fires in Siberia, remarkable by their abnormal intensity in this year.